Neuromuscular Adaptations to Multimodal Injury Prevention Programs in Youth Sports: A Systematic Review with Meta-Analysis of Randomized Controlled Trials - Faude, Oliver; Rössler, Roland; Petushek, Erich J.; Roth, Ralf; Zahner, Lukas; Donath, Lars (Frontiers in Physiology, 2017)
Objective: Neuromuscular injury prevention programs (IPP) can reduce injury rate by about 40% in youth sport. Multimodal IPP include, for instance, balance, strength, power, and agility exercises. Our systematic review and meta-analysis aimed to evaluate the effects of multimodal IPP on neuromuscular performance in youth sports. Methods: We conducted a systematic literature search including selected search terms related to youth sports, injury prevention, and neuromuscular performance. Inclusion criteria were: (i) the study was a (cluster-)randomized controlled trial (RCT), and (ii) investigated healthy participants, up to 20 years of age and involved in organized sport, (iii) an intervention arm performing a multimodal IPP was compared to a control arm following a common training regime, and (iv) neuromuscular performance parameters (e.g., balance, power, strength, sprint) were assessed. Furthermore, we evaluated IPP effects on sport-specific skills. Results: Fourteen RCTs (comprising 704 participants) were analyzed. Eight studies included only males, and 5 only females. Seventy-one percent of all studies investigated soccer players with basketball, field hockey, futsal, Gaelic football and hurling being the remaining sports. The average age of the participants ranged from 10 years up to 19 years and the level of play from recreational to professional. Intervention durations ranged from 4 weeks to 4.5 months with a total of 12 to 57 training sessions. We observed a small overall effect in favor of IPP for balance/stability (Hedges´g=0.37; 95%CI 0.17,0.58), leg power (g=0.22; 95%CI 0.07,0.38) and isokinetic hamstring and quadriceps strength as well as hamstrings-to-quadriceps ratio (g=0.38; 95%CI 0.21,0.55). We found a large overall effect for sprint abilities (g=0.80; 95%CI 0.50,1.09) and sport-specific skills (g=0.83; 95%CI 0.34,1.32). Subgroup analyses revealed larger effects in high-level (g=0.34-1.18) compared to low-level athletes (g=0.22-0.75), in boys (g=0.27-1.02) compared to girls (g=0.09-62 0.38), in older (g=0.32-1.16) compared to younger athletes (g=0.18-0.51) and in studies with high (g=0.35-1.16) compared to low (g=0.12-0.38) overall number of training sessions. Conclusion: Multimodal IPP beneficially affect neuromuscular performance. These improvements may substantiate the preventative efficacy of IPP and may support the wide-spread implementation and dissemination of IPP.